An Empirical Study of Selected Factors Influencing the Decision to List on Foreign Stock Exchanges - Saudagaran, Shahrokh M. (Journal of International Business Studies, 1988)
The growing internationalization of capital markets suggests that an increasing number of firms perceive the benefits of listing their stocks on foreign exchanges as outweighing the related costs. Many other firms, however, still limit listing their securities to their domestic exchanges. This study investigates the motives for listing abroad. The empirical analyses, based on data on 481 multinationals, indicate significant association between the likelihood of listing abroad and 1) the relative size of a firm in its domestic capital market, 2) the ratio of foreign to total sales.